Polymeric materials and films in dentistry: An overview - Dinesh Rokaya; Viritpon Srimaneepong; Janak Sapkota; Jiaqian Qin; Krisana Siraleartmukul; Vilailuck Siriwongrungson (My University, 2018)
The use of polymeric materials (PMs) and polymeric films (PMFs) has increased in medicine and dentistry. This increasing interest is attributed to not only the excellent surfaces of PMs and PMFs but also their desired mechanical and biological properties, low production cost, and ease in processing, allowing them to be tailored for a wide range of applications. Specifically, PMs and PMFs are used in dentistry for their antimicrobial, drug delivery properties; in preventive, restorative and regenerative therapies; and for corrosion and friction reduction. PMFs such as acrylic acid copolymers are used as a dental adhesive; polylactic acids are used for dental pulp and dentin regeneration, and bioactive polymers are used as advanced drug delivery systems. The objective of this article was to review the literatures on the latest advancements in the use of PMs and PMFs in medicine and dentistry. Published literature (1990–2017) on PMs and PMFs for use in medicine and dentistry was reviewed using MEDLINE/PubMed and ScienceDirect resources. Furthermore, this review also explores the diversity of latest PMs and PMFs that have been utilized in dental applications, and analyzes the benefits and limitations of PMs and PMFs. Most of the PMs and PMFs have shown to improve the biomechanical properties of dental materials, but in future, more clinical studies are needed to create better treatment guidelines for patients.
Keywords: Dental materials and restorations